VLA15 - a potential Lyme disease vaccine - Czarnota, Jakub; Dobrzyński, Michał; Skubel, Tomasz; Drozd, Małgorzata; Dudek, Iga; Rybak, Natalia (Journal of Education, Health and Sport, 2022)
Introduction: Lyme disease is the most common disease transmitted by ticks. In Poland, over 20,000 cases of this disease were diagnosed in 2019. The first vaccine approved to prevent this condition was Lymerix. Currently, we do not have any preparation registered for this purpose. Data from Phase 2 trials of VLA15 show strong immunogenicity in both adults and children, with an acceptable safety and tolerability profile in both study populations Aim: The purpose of this paper is to present the current state of the art in research into the VLA15 vaccine. Results: Phase 3 of the VALOR study has started. Ultimately, about 6,000 participants aged 5 and older are to take part in it. The experiment is conducted in a dozen or so sites located in areas where Lyme disease is highly endemic. Participants will receive three doses of VLA15 180 µg or a placebo in saline as the first series of vaccinations, followed by one booster dose of VLA15 or placebo in 0.9% NaCl (1: 1 ratio). Conclusion: Phase 2 studies on VLA15 showed promising results. Phase 3 of the research is ongoing. Key words: VLA15, Lyme disease, Borrelia